Functional protein materials: beyond elastomeric and structural proteins. Issue 23 (22nd May 2019) - Carter, Nathan A.; Grove, Tijana Z.
Abstract : In the past two decades researchers have shown great interest in mimicking biological structures and their complex structure–property relationships. Herein we highlight examples of hydrogels and bioelectronic materials that illustrate the rational design of material properties and function. Abstract : In the past two decades researchers have shown great interest in mimicking biological structures and their complex structure–property relationships that have evolved from a small number of chemically similar building blocks. The great strides in this field are evident in bio-inspired materials and structures that are making their way into commercial products. Among natural biopolymers, proteins provide a versatile building block with inherent structural and functional complexity that is unmatched by synthetic materials. Herein, we review recent strategies to influence the self-assembly of protein materials whose hierarchical structure may prove useful in a variety of applications, for example in soft-robotics and energy storage.